Abortion Across State Lines - Dellapenna, Joseph W. (2008)
In this Article, I propose to analyze conflicts of law precedents and theory to explore the extent to which a state can apply its law on abortion to abortions performed outside the state but bearing a significant connection to the state. In attempting to resolve such questions, we enter into the domain of choice of law, part of the field of conflicts of law. This domain is notoriously unstable and contested. This instability allows legal commentators to project their attitudes towards abortion (and many other matters) in analyzing and construing the relevant authorities to resolve choice of law issues. I shall strive to avoid doing that, but it is for others to decide whether I succeed. I begin in Part I by examining why differences among states regarding abortion policy arise and why those difference are likely to persist. I then proceed in Part II by describing choice of law theory generally. In Part III, I examine the application of choice of law theory to litigation involving differing abortion laws in different states. I conclude in Part IV that states can apply their laws to their citizens when they travel out of the state in an effort to avoid abortion restrictions